Respuesta :
X=2
All this stuff is wrong I screwed up somewhere:
IGNORE EVERYTHING BELOW THIS:
take the natural log of both sides of the equation.
[tex] ln(( \frac{4}{9})^{x} ) \times \ ln(( \frac{8}{27})^{(1 - x)} ) = ln( \frac{2}{3} ) [/tex]
Remembering your log rules:
[tex] ln( {a}^{b} ) = b \: ln(a) [/tex]
Using this rule we rewrite the first equation:
[tex]x \: ln( \frac{4}{9} ) \times (1 - x) \: ln( \frac{8}{27} ) = ln( \frac{2}{3} ) [/tex]
Simplify:
[tex]x ln( \frac{4}{9} ) \times ( ln( \frac{8}{27}) - x \: ln( \frac{8}{27} ) ) [/tex]
Solve for some of these ln's to make life easier:
[tex] - .81x \: \times ( - 1.22 - 1.22x) = - .41[/tex]
Distribute:
[tex](.988x + .988x^{2} ) = - .41[/tex]
Factor out .988
[tex].988(x + {x}^{2} ) = - .41 \\ (x + {x}^{2} ) = \frac{ - .41}{.988} \\ (x + {x}^{2} ) = - .415[/tex]
All this stuff is wrong I screwed up somewhere:
IGNORE EVERYTHING BELOW THIS:
take the natural log of both sides of the equation.
[tex] ln(( \frac{4}{9})^{x} ) \times \ ln(( \frac{8}{27})^{(1 - x)} ) = ln( \frac{2}{3} ) [/tex]
Remembering your log rules:
[tex] ln( {a}^{b} ) = b \: ln(a) [/tex]
Using this rule we rewrite the first equation:
[tex]x \: ln( \frac{4}{9} ) \times (1 - x) \: ln( \frac{8}{27} ) = ln( \frac{2}{3} ) [/tex]
Simplify:
[tex]x ln( \frac{4}{9} ) \times ( ln( \frac{8}{27}) - x \: ln( \frac{8}{27} ) ) [/tex]
Solve for some of these ln's to make life easier:
[tex] - .81x \: \times ( - 1.22 - 1.22x) = - .41[/tex]
Distribute:
[tex](.988x + .988x^{2} ) = - .41[/tex]
Factor out .988
[tex].988(x + {x}^{2} ) = - .41 \\ (x + {x}^{2} ) = \frac{ - .41}{.988} \\ (x + {x}^{2} ) = - .415[/tex]
[tex](\frac{4}{9})^x\cdot (\frac{8}{27})^{1-x} =\frac{2}{3}\\((\frac{2}{3})^2)^x\cdot ((\frac{2}{3})^3)^{1-x} =\frac{2}{3}\\(\frac{2}{3})^{2x}\cdot (\frac{2}{3})^{3-3x} =\frac{2}{3}\\(\frac{2}{3})^{2x+3-3x} =\frac{2}{3}\\(\frac{2}{3})^{-x+3} =\frac{2}{3}\\-x+3=1\\-x=1-3\\-x=-2\ /:(-1)\\x=2[/tex]